2021
DOI: 10.3390/coatings11050547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrier Gas Flow Field on Chemical Vapor Deposition of 2D MoS2 Crystal

Abstract: The carrier gas flow field plays a vital role in the chemical vapor deposition (CVD) process of two dimensional (2D) MoS2 crystal, which was studied by simulations and experiments. Different carrier gas flow fields were studied by utilizing three types of precursor carrier which affected the local gas flow field significantly. The experiment results showed that the appropriate precursor vapor concentration could be achieved by local carrier gas flow field conditioning, resulting in single 2D MoS2 crystals of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Various intrinsic lattice defects including vacancies, substitutional impurities, adatoms, antisite defects, and grain boundaries are frequently observed in TMDs, mostly resulted from a variety of non-optimized growth conditions. Laminarity of the precursor vapor flow is of vital importance for the growth of high-quality 2D crystals as it is controlling the crystallinity by directly affecting the structural defect density [22,29,37]. We did not observe any variation in the Raman spectra considering the change in flow direction.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Various intrinsic lattice defects including vacancies, substitutional impurities, adatoms, antisite defects, and grain boundaries are frequently observed in TMDs, mostly resulted from a variety of non-optimized growth conditions. Laminarity of the precursor vapor flow is of vital importance for the growth of high-quality 2D crystals as it is controlling the crystallinity by directly affecting the structural defect density [22,29,37]. We did not observe any variation in the Raman spectra considering the change in flow direction.…”
Section: Resultsmentioning
confidence: 55%
“…Bai et al investigated how MoS 2 grain size is affected by the gas flow concentration around the substrate surface using differently shaped quartz crucibles. They showed that reduced velocity or pressure led to an increased MoS 2 grain size, which could result from longer residence times on the surface [29]. The flow perpendicular to the microchannels may give rise to the augmentation of the number of vortices enhancing the intensity of the turbulence around the channels resulting in non-uniform dispersion [21].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that sodium ions enhance the growth rate by reducing the energy barrier for MoS 2 growth and promote film formation by forming an intermediate product with a lower melting point than MoO 3 [34][35][36]. The CVD process can be outlined in five key steps: (a) sublimation of precursors and transport by a carrier gas; (b) diffusion towards the substrate; (c) surface adsorption; (d) spreading of adatoms across the surface; and (e) the occurrence of the reaction to form flakes/film [37]. The efficiency of precursor transport is directly dependent on the carrier gas.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a large number of MoS 2 molecules accumulate on the substrate to deposit a continuous MoS 2 monolayer structure. In other words, higher concentrations of molybdenum and sulfur vapor allow for larger-sized MoS 2 crystal fragments or more of the target area to be covered with MoS 2 [43]. For open-ended quartz boat, the different distributions of MoS 2 structures on SiO 2 /Si substrate are also investigated (see Fig.…”
Section: Resultsmentioning
confidence: 99%